Back Cover: Locating Gases in Porous Materials: Cryogenic Loading of Fuel‐Related Gases Into a Sc‐based Metal–Organic Framework under Extreme Pressures (Angew. Chem. Int. Ed. 45/2015). Issue 45 (22nd September 2015) - Sotelo, Jorge; Woodall, Christopher H.; Allan, Dave R.; Gregoryanz, Eugene; Howie, Ross T.; Kamenev, Konstantin V.; Probert, Michael R.; Wright, Paul A.; Moggach, Stephen A.
Abstract : A cryogenic technique for loading a porous metal–organic framework with gas molecules is described by S. A. Moggach et al. in their Communication onpage 13332 ff. The technique, usually used by physicists and planetary scientists, involves loading gases cryogenically into a diamond anvil cell. Here, both CO2 and CH4 were loaded into a scandium‐based MOF. On increasing pressure the presence of a previously unobserved adsorption site was elucidated, and the pores were "superfilled" with guest molecules at room temperature.